Early Upper Paleolithic subsistence in the Levant: Zooarchaeology of the Ahmarian–Aurignacian sequence at Manot Cave, Israel. Issue 160 (November 2021) - Yeshurun, Reuven; Schneller-Pels, Nehora; Barzilai, Omry; Marder, Ofer
Abstract: The Early Upper Paleolithic period in the Levant is essential in the studies of the establishment of modern human communities outside Africa, and corresponding archaeological evidence may be used to shed light on human ecology, economy and demography. Specifically, cultural differences between two Early Upper Paleolithic entities, the Early Ahmarian and the Levantine Aurignacian, raise the question of differing adaptations. In this article we use archaeofaunal remains from the Early Upper Paleolithic sequence at Manot Cave (Western Galilee, Israel), to track human hunting patterns, carcass transport and processing within the Early Ahmarian (46–42 ka) and Levantine Aurignacian (38–34 ka) phases. We test two hypotheses: 1) the Ahmarian and Aurignacian represent adaptations to different environments; and 2) the two entities differ in mobility patterns and site use. Our multivariate taphonomic analysis showed subtle differences in depositional processes between the two phases and demonstrated a primarily anthropogenic complex. In both phases, human subsistence was based on two ungulate species, mountain gazelle ( Gazella gazella ) and Mesopotamian fallow deer ( Dama mesopotamica ), with some contribution from birds, tortoises and small mammals. Among the gazelles, it appears that female herds were targeted, and that hunting took place close to the cave. The results of the research show great similarity in environmental exploitation between the Ahmarian and Aurignacian phases concerning prey spectrum and choice, carcass transport and processing. These patterns occupy a middle position between the Middle Paleolithic and the late Epipaleolithic of the region. Despite this, there are also several significant differences between the phases such as increased exploitation of small game (especially birds) and faster accumulation and higher densities of material in the Aurignacian. This may indicate greater occupation intensity during the Aurignacian compared to the Ahmarian, and thus could explain the outstanding character of this entity in the Levant.